Regularitas Operator Potensial Layer Tunggal - Wono Setya Budhi (Jurnal Matematika & Sains, 1997)
We prove the regularity of the operator Î©ââ=â«Î©xdsxxu)()(||ln21)(Î¾Î¾ÏÎ¾Ïâ using similar technique for proving Cauchy integral operator. If Ï are continue on âÎ©, we prove that u is uniformly Holder continue in Î© with Holder exponent Î± for every Î± â (0,1). However, from the proof, if uL then u is in the same space as before.